Implementation of a Synergetic Controller for a 2-DOF Helicopter on an Embedded Platform Using an STM32 Microcontroller - Chiem, Nguyen Xuan; Phan, Tran Cong; Thai, Pham Duy; Hai, Bui Xuan (Universitas Ahmad Dahlan, 2025)
This study introduces the development of a synergetic control scheme for a two-degree-of-freedom (2-DOF) helicopter, integrated into an embedded system utilizing the STM32 microcontroller. A discrete-time controller is formulated for both pitch and yaw motion, relying on stable manifold design within the framework of synergetic control. Lyapunov-based analysis is used to ensure system stability. The controller is implemented on an STM32F4 device and coded in the C programming language. System performance is assessed through numerical simulations and real-time testing, with results demonstrating strong control precision and feasibility on the physical experimental platform.